Identification of (Poly)phenolic compounds in concord grape juice and their metabolites in human plasma and urine after juice consumption - Stalmach, A.; Edwards, Christine; Wightman, J.; Crozier, A. (2011)
Analysis of Concord grape juice by HPLC with ESI-MSn, PDA, and fluorescence detection resulted in the identification and quantification of 60 flavonoids and related phenolic compounds, which were present at an overall concentration of 1508 ± 31 μmol/L. A total of 25 anthocyanins were detected, which were mono- and di-O-glucosides, O-acetylglucosides, O-p-coumaroyl-O-diglucosides, and O-p-coumaroylglucosides of delphinidin, cyanidin, petunidin, peonidin, and malvidin. The anthocyanins represented 46% of the total phenolic content of the juice (680 μmol/L). Tartaric esters of hydroxycinnamic acids, namely, trans-caftaric and trans-coutaric acids, and to a lesser extent trans-fertaric acid accounted for 29% of the phenolic content, with a total concentration of 444 μmol/L, of which 85% comprised trans-caftaric acid. Free hydroxycinnamic acids were also quantified but contributed to <1% of the total phenolic content (8.4 μmol/L). The other groups of polyphenolic compounds present in the juice, accounting for 24% of the total, comprised monomeric and oligomeric units of (epi)catechin and (epi)gallocatechin (248 μmol/L), flavonols (76 μmol/L), gallic acid (51 μmol/L), and trans-resveratrol (1.5 μmol/L). The bioavailability of the (poly)phenolic compounds in 350 mL of juice was investigated following acute intake by healthy volunteers. Plasma and urine were collected over 0–24 h and analyzed for parent compounds and metabolites. In total, 41 compounds, principally metabolites, were identified.